Who is watching: exploring individual factors that explain supervision patterns among residential guardians - Reynald, Danielle M. (2019)
Supervision has been identified within criminology as an important element of crime prevention; however, little is known about the individual factors that explain this behaviour among residential guardians. Unique self-report data on daily surveillance routines of residents were gathered from a national sample of 4824 respondents in the Netherlands to explore the key factors that facilitate and inhibit supervision. It was tentatively estimated that residents carry out supervision roughly a quarter of the time they are at home. Further analyses revealed that individual resident characteristics, such as their perceptions of crime, sense of responsibility for guarding, security training, courageousness and national security values positively predict supervision intensity. Conversely, self-esteem and trust were found to negatively affect supervision. Results suggest that manipulable individual factors such as attitudes are more important at predicting supervision than comparatively static factors such as personality. Implications for criminological theory that explains the concept of supervision as a function of guardianship, and how it can be fostered as a crime control mechanism within residential contexts, will be discussed.